MANUSIA DALAM PANDANGAN FILSAFAT - Heru Syahputra (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
Human are the most unique creatures that have obligations and responsinilities. Thanks to the psychic power of creativity, taste and work, man can know that he knows and also he knows that he is in a state of not knowing. Than other creatures, with psychic power humans have advantages, which is able to face every problem of life. Whether the view is concerned with oneself, others individually and socially with nature or with the creator. With the potential of reason can now clarify the basis and purpose of it existence as humans. Whereas philosophy has different conditions and fertile life in the actualization of diverse human conditions. So it can be concluded that because of philosophy, a creature can become a human being, and because human are certainly philosophical. Philosophy becomes a characteristic of humans.Keywords: Human, View, Philosophy.